2004
DOI: 10.1071/wr03096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sample age and season of collection on the reliability of microsatellite genotyping of faecal DNA

Abstract: Individual identification of animals from DNA in field-collected faecal samples is becoming an increasingly important tool in wildlife population monitoring. A major issue relevant to the application of this technique is the reliability of the genotypes obtained. I investigated the effect of sample age and season of collection on amplification rates and reliability of microsatellite genotypes amplified from faecal DNA of a marsupial herbivore, the brush-tailed rock-wallaby (Petrogale penicillata) and a eutheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
167
2
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(189 citation statements)
references
References 32 publications
15
167
2
5
Order By: Relevance
“…In such a case, several points should be kept in mind. As for factors related to the DNA condition, climate including temperature, humidity and rainfall, as well as diet or elapsed time from defecation are suggested [3,17,24]. For feces in a low DNA condition, repeating fecal DNA extraction or PCR amplification will be needed due to allelic dropout and false alleles resulting from DNA degradation [2,11,25].…”
Section: Discussionmentioning
confidence: 99%
“…In such a case, several points should be kept in mind. As for factors related to the DNA condition, climate including temperature, humidity and rainfall, as well as diet or elapsed time from defecation are suggested [3,17,24]. For feces in a low DNA condition, repeating fecal DNA extraction or PCR amplification will be needed due to allelic dropout and false alleles resulting from DNA degradation [2,11,25].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, climatic conditions and air moisture may play an important role in DNA preservation. For example, Brinkman et al (2010) reported high degradation of fecal DNA that was exposed to rainfall while Piggott (2005) obtained higher DNA quality from feces samples that were collected during summer. Because of the dry climatic conditions of our study region (Di Castri and Hajek, 1976), DNA degradation in L. guanicoe feces might be relatively slow and facilitate the amplification of small PCR products from non-fresh fecal material.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Fecal samples were collected opportunistically during each trap event. Because DNA quality is affected by fecal sample age [30,41], we ensured collection of fresh fecal samples by only using feces collected in the mesh handling bag rather than the trap. We collected all intact pellets with forceps and transferred whole pellets directly to 95% ethanol for storage; broken pellets were avoided and care was taken to avoid crushing the pellets during collection and transfer [42].…”
Section: Study Site and Sample Collectionmentioning
confidence: 99%